2021
DOI: 10.1002/brb3.2383
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural prevalence of sleep quality and psychological distress in healthcare workers during COVID‐19 pandemic

Abstract: Background: Poor quality sleep and emotional disturbances are expected in times of crisis. COVID-19 has severely impacted healthcare worldwide and with that comesThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…In our study, almost half of the HCPs (52.7%) were found to be poor sleepers during this pandemic, which is in line with a study from China and a multicenter study from India, China, and Nepal [26,36]. The prevalence of sleep disorders during the COVID-19 pandemic was reported to range from 18.5% to 61% [37][38][39].…”
Section: Categories Of Psqisupporting
confidence: 91%
“…In our study, almost half of the HCPs (52.7%) were found to be poor sleepers during this pandemic, which is in line with a study from China and a multicenter study from India, China, and Nepal [26,36]. The prevalence of sleep disorders during the COVID-19 pandemic was reported to range from 18.5% to 61% [37][38][39].…”
Section: Categories Of Psqisupporting
confidence: 91%
“…The median number of participants was 338. Excluding manuscripts that reported age as range or median (i.e., 28%) [ 41 , [44] , [45] , [46] , 48 , 59 , [61] , [62] , [63] , 69 , 73 , 75 ], [ 84 , 87 , 96 , [98] , [101] , 104 , 111 , 112 , 121 ], [ 126 , 134 , 137 , 141 , 144 , 145 , 147 ], [ 158 , 161 , [163] , [164] , [165] , 167 , 169 , 175 ], the mean age of the participants was 32.22 ± 9.35 years. Regarding the administered sleep measures, 103 studies reported PSQI scores.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“…This may be because the mortality rate between January 2020 and September 2020 in Japan (1.88%) was higher than that in Singapore (0.05%), indicating that the frontline nurses and physicians in Japan needed to take care of dying patients and interact with the families of deceased patients more often ( 30 ). Management may also have affected the levels of psychological distress, as a previous study revealed that higher levels of psychological distress were associated with COVID-19 procedural management ( 31 ). Finally, differences in culture, medical systems, and demographic factors of participating healthcare providers in each country may have contributed to this disparity.…”
Section: Discussionmentioning
confidence: 99%